2022
DOI: 10.1007/s10549-022-06722-0
|View full text |Cite
|
Sign up to set email alerts
|

Highly accurate response prediction in high-risk early breast cancer patients using a biophysical simulation platform

Abstract: Purpose Pathologic complete response (pCR) to neoadjuvant chemotherapy (NAC) in early breast cancer (EBC) is largely dependent on breast cancer subtype, but no clinical-grade model exists to predict response and guide selection of treatment. A biophysical simulation of response to NAC has the potential to address this unmet need. Methods We conducted a retrospective evaluation of a biophysical simulation model as a predictor of pCR. Patients who received s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 33 publications
1
18
1
Order By: Relevance
“…The pCR rate in the I-SPY2 trial with pembrolizumab and SOC chemotherapy was 60% in TNBC and 30% in HR+/HER2cancers (Nanda et al, 2020), while the GIADA trial demonstrated a pCR rate of 16.3% in IO-treated HR+/HER2-patients (Franzoi et al, 2021;Dieci et al, 2022). The success of this validation strategy supports the potential for expansion of virtual clinical trials in both research and drug development applications (Howard et al, 2022). Additionally, this result signals the potential of the TumorIO Score to accurately predict ICI responsiveness and provide a strong correlation to randomized control trials.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The pCR rate in the I-SPY2 trial with pembrolizumab and SOC chemotherapy was 60% in TNBC and 30% in HR+/HER2cancers (Nanda et al, 2020), while the GIADA trial demonstrated a pCR rate of 16.3% in IO-treated HR+/HER2-patients (Franzoi et al, 2021;Dieci et al, 2022). The success of this validation strategy supports the potential for expansion of virtual clinical trials in both research and drug development applications (Howard et al, 2022). Additionally, this result signals the potential of the TumorIO Score to accurately predict ICI responsiveness and provide a strong correlation to randomized control trials.…”
Section: Discussionmentioning
confidence: 70%
“…We then correlated single cell PD-L1 expression with transcriptional biomarkers related to metabolic activity ( Supplementary Figures 1 , 2 ) and angiogenesis ( Supplementary Figure 3 ). PD-L1 expression throughout the tumor cannot be visualized using SOC imaging; therefore, as a surrogate for spatially-resolved PD-L1 expression, we simulated and quantified the spatial distribution of both metabolic activity and angiogenesis within individual patient tumors and the TME using the Simul- omics 4D Engine (Howard et al, 2022 ). This analysis resulted in a spatial map of biological features correlated with PD-L1 expression probability, which together underly the TumorIO spatial biomarker.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations